2015
DOI: 10.1016/j.febslet.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linking analysis reveals the putative dimer structure of the cyanobacterial BLUF photoreceptor PixD

Abstract: a b s t r a c tPixD is a blue light using flavin (BLUF)-type blue-light photoreceptor controlling phototaxis in the cyanobacterium Synechocystis sp. PCC6803. The crystal structure of PixD shows a decamer, although in solution an equilibrium is maintained between the dimer and decamer. Because the ratio of these two conformers is altered by illumination, the equilibrium state determines photosensitivity. However, no structural information is available for the PixD dimer. Here, we report a predicted structure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…These results underscore the importance of interactions between the C-terminus of two PixD molecules to form a dimer. When the C-terminal region of PixD is removed, PixD does not form a stable dimer, a finding that further supports the PixD dimeric structural model (Ren et al 2015 ). The in-silico modeled PixD dimer is not similar to any dimeric combination found in the PixD crystal structure (Fig.…”
Section: Pixd-dependent Signal-relay Mechanismssupporting
confidence: 63%
See 4 more Smart Citations
“…These results underscore the importance of interactions between the C-terminus of two PixD molecules to form a dimer. When the C-terminal region of PixD is removed, PixD does not form a stable dimer, a finding that further supports the PixD dimeric structural model (Ren et al 2015 ). The in-silico modeled PixD dimer is not similar to any dimeric combination found in the PixD crystal structure (Fig.…”
Section: Pixd-dependent Signal-relay Mechanismssupporting
confidence: 63%
“…Crystalline PixD forms a decamer in which two pentameric rings are stacked face-to-face (Yuan et al 2006 ). Gel-filtration and blue-native PAGE studies have revealed that purified PixD equilibrates between a dimer and decamer in solution (Ren et al 2013 , 2015 ; Tanaka et al 2011 ; Yuan and Bauer 2008 ), suggesting that the crystal structure of decameric PixD possibly reflects a decameric structure in vivo. Conversely, a solution structure for dimeric PixD has not been established.…”
Section: Pixd-dependent Signal-relay Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations